PENDAYAGUNAAN HAK INISIATIF ANGGOTA DPRD DALAM PEMBENTUKAN PERATURAN DAERAH (STUDI YURIDIS SOSIOLOGIS DI DPRD SULAWESI SELATAN) - Dayanto Dayanto (IAIN Ambon, 2017)
This research aims to analyze the utilization of initiative right of South Sulawesi Provincial Parliament’s members in the Regional regulations establishment and to analyze the factors wich influences the effectiveness of it. This research did at South Sulawesi Legislative Assembly at Provincial Level. The method which used in this research was juridical sociology with collecting data by the way of studying the document, interview, and observation. The data was analyzed by using qualitative analysis which combined with quantitative analysis (frequency tabulation). The result revealed that (1) utilization of the initiative right of South Sulawesi Provincial Parliament’s members in the Regional regulations establishment does not effective yet; (2) Such as this was influenced by : (a) human resource of Provincial Parliament’s members and (b) the public control and public partisipation in the establishment of Regional regulations. Keyword: The initiative right, Regional regulations